A sinkhole prevention mechanism for RPL in IoT. (25th November 2020) - Mishra, Alekha Kumar; Sinha, Maitreyee; Tripathy, Asis Kumar
A sinkhole node has the ability to redirect all the traffic routes from IoT nodes to the root (sink) node through it with the help of false rank advertisement. Unfortunately, there is no provision for a node to verify the actual rank received by a claiming parent from its parent in the RPL protocol. A number of sinkhole and rank spoofing detection mechanisms have been proposed in the literature. The works claiming higher detection rate mostly use cryptography-based operations, which incurs additional computational overhead. In this paper, a sinkhole prevention mechanism is proposed that decides the legitimacy of a node in the neighbourhood by considering three network metrics. These are hop count, residual energy, and expected transmission count (ETX). The mechanism relies on the fact that all the nodes in a neighbourhood have similar network metrics with respect to the position of the root node in the network. Therefore, a node claiming to have metric values quite different from the mean in a neighbourhood is identified as a sinkhole. The experimental results show that the proposed mechanism can significantly distinguish a sinkhole node from genuine ones in arbitrary locations in the network.